Brand Positioning of the Sport Sciences Research Institution of Iran using Perceptual Mapping Technique - Mehdi Rasouli; Mahmood Fazel Bakhsheshi; hossein zareian (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Brands are the most important source of emotional attachment with the consumer, it should be used as a vital tool for attracting and retaining customers of the organization and various sports organizations, should follow the theoretical principles related to brand management and brand loyalty and move towards strategic brand management as a superior marketing philosophy. Objectives. The purpose of this research was to position the Sport Sciences Research Institution of Iran using the Perceptual Mapping Technique. Methods. Competitive characteristics and strategic rivals of the Sport Sciences Research Institution were obtained from Rasooli Research (2013). Competitive characteristics and competitors were then prioritized using a researcher-made questionnaire and hierarchical method. The statistical population of this research consisted of the academic staff of the country including faculty members and graduate students. Analytic hierarchy analysis was used to prioritize the research variables. Results. Based on the obtained results, perceptual maps of the brand position of the research Center were depicted. The results showed that the position of brand of Sport Sciences Research Institution among academic researchers of the country in terms of research services, facilities and products was higher than other competitors while the field of educational services after physical education faculties was in the second place; and effort should be made in this area to promote their brand. Conclusion. In the competitive and turbulent environment of today, the role of brand as consumers' decision-making guide is becoming more important. Branding should therefore be considered as a continuous activity in all modes.